Project-Based Collaborative Writing In Teaching Grammar For Students With High And Low Motivation - Nurcahyoko, Kunto ((JELE) Journal Of English Language and Education, 2015)
Although the body of literature has been supporting the use of Project-BasedCollaborative Writing (PBCW) to teach grammar, there is still huge urgency tomeasure its effectiveness for language learners with different motivation. This studyaims to investigate the effectiveness of PBCW, the effect of motivation in teachinggrammar for ten graders,and the interaction among techniques, motivation, andstudents’ grammar. The study employed a 2X2 factorial research design involving 48students in two experimental groups and two control groups. The samples were dividedinto students with high and low motivation group. The data were collected by usingpretest and posttest techniques. Statistical Package for Social Sciences (SPSS) was usedfor analyzing the data. The result showsthat project-based collaborative writing andcollaborative learning techniques are more effective to be used to teach grammar forstudents with high motivation as compared to students with low motivation. The resultalso reveals that motivation does not really affect the students’ grammar performance.However, there is still different improvement between students with low and highmotivation in their grammatical accuracy. Lastly, the analysis of variance shows thatthere is no interaction among students’ motivation, techniques, and students’ grammarwith the level of significance at 0.934. The study suggests that teachers must be able toconsider the presence of both variables in teaching and learning, especially to teachgrammatical accuracy.Keywords : Project-based collaborative learning (PBCW), collaborative learning, highand low motivation, grammar